Business Retention and Expansion (BRE) Programs: Preparing a Community Assessment - Henry M. Cothran (EDIS)
FE659, a 4-page fact sheet by Henry M. Cothran, is part of the Business Retention and Expansion programs (BREs) series. It explains what a community assessment is, how it is used, what information is included, and how to find information for the assessment. Includes references. Published by the UF Department of Food and Resource Economics, January 2009. Reviewed January 2012.